Socialization of the Use of Corn Husk Waste to Micro, Small and Medium Enterprises (MSME) in Mampang Prapatan Subdistrict, South Jakarta City: Sosialisasi Pemanfaatan Limbah Kulit Jagung pada Pelaku Usaha Mikro, Kecil dan Menengah (UMKM) di Kecamatan Mampang Prapatan, Kota Jakarta Selatan - Harlina, Harlina Kusuma Tuti (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
Corn plants is one of the flora that is used as a staple food to replace rice. Corn plants produce 95% of waste, with that much waste, if it is not managed properly there will be piles of rubbish, and can cause damage to environmental sustainability. Therefore, socialization is needed regarding the use of corn husk waste among MSME. The method used is counseling with the approach used in the form of lectures, motivation and discussions. In community service activities, based on participant characteristics, it was found that the majority of MSME in Mampang Prapatan District, South Jakarta City have businesses based on craft innovation. Corn husk waste can be turned into material for making innovative craft products. The process of making product ingredients from corn husk waste: preparation, preservation, bleaching and coloring. Various products can be made from corn husk waste: dried flowers, bags, dolls, and tissue holders.